The Effect of Social Support and Resilience on Psychological Well-Being, With Self-Acceptance as A Mediating Variable, Among Employees of Pertamina’s Upstream Subholding - Hary Kuswanto; Abdurrohim Abdurrohim; Zamroni Zamroni (International Journal Labs, 2026)
Psychological well-being is critical for employees in high-risk industries such as oil and gas due to intensive job demands, remote working conditions, and safety risks that may increase stress levels. This study, The Effect of Social Support and Resilience on Psychological Well-Being, With Self-Acceptance as a Mediating Variable, Among Employees of Pertamina’s Upstream Subholding, aims to examine the influence of social support and resilience on psychological well-being, with self-acceptance as a mediating variable among employees of Pertamina Subholding Upstream. A quantitative survey design was applied, involving 383 employees selected using the Slovin formula and purposive sampling techniques. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. Findings indicate that social support and resilience have positive and significant effects on both self-acceptance and psychological well-being. The model demonstrates moderate explanatory power, with an R² value of 0.430 for psychological well-being. Psychological well-being is influenced by both external factors (social support) and internal factors (resilience and self-acceptance). Strengthening workplace support systems and individual psychological resources is essential to enhancing employee well-being and organizational performance in high-risk industrial settings. These findings highlight the importance of integrated mental health strategies within organizations, particularly through strengthening supportive leadership, peer relationships, and resilience-based interventions to improve employee well-being and sustain long-term productivity in the energy sector context.